EFFECTS OF POULTRY MANURE AND WEED CONTROL METHODS ON GROWTH AND YIELD OF SESAME VARIETIES - Danmaigoro, O.; Zamfara, M. I.; Yakubu, H.; Umar, Musa M. (FUDMA Journal of Sciences, 2020)
Field trials were conducted in 2017 and 2018 wet seasons at Federal University Dutse Teaching and Research Farm (Latitude 11 46, 39â€N and Longitude 9 20, 30â€E) in the Sudan Savanna of Nigeria. To evaluate performance of sesame varieties as affected by poultry manure and weed control methods. The treatments consisted of five weed control treatments (pre-emergence application of ButachlorEC50%, hoe weeding at 3WAS +pre-emergence butachlor EC50%, pre-emergence butachlor EC50%+hoe weeding at 3 and 6WAS, hoe weeding @ 3 and 6WAS and weedy check), three level of poultry manure (5, 10, and 15t/ha) and three sesame varieties (Ben 01, Yandev 55 and Ben 04E. The treatments were laid out in split plot design and replicated three times. The results indicated that weed control methods had significant effect (0.05) on the sesame growth and seed yield comparable to hoe weeding control at 3 and 6WAS where plant height number of leaves, capsule number per plant and seed yield of sesame were significant higher with the application of butachlor plus hoe weeding at 3 and 6WAS compared to others weed control methods. Poultry manure application on sesame as 15t/ha gave taller plant height, more number of leaves, higher sesame dry weight, longer capsule length and seed yield of sesame than the other rates while Ben 01(455 and 1043 ) perform better than the others two varieties (Yandev 498, 756 and Ben4E 522 and 765 ) for 2017 and 2018 seasons. In conclusion,